PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI STATISTIK PARAMETRIK MENGGUNAKAN PROGRAM FLASH MATA KULIAH STATISTIKA INFERENSIAL - Jainuri, M. (MAT-EDUKASIA, 2018)
The purpose of this research is to know the procedure of development of interactive multimedia learning and to produce flash-based program of parametric statistics material in Inferential Statistics Course, and to know student's response. The research method used is development research, with material selection procedure, user determination, determining program indicator, arranging scenario, making design appearance, making prototype, testing, and evaluation. The program is validated by material experts and media experts then tested. Assessment of material experts concluded that the program is very feasible to use with a percentage of 95%, and the assessment by the program media experts declared very feasible with the percentage of 84%. The student's response to the program is excellent with a percentage of 86.98%. The conclusion of this research is the interactive multimedia of parametric statistical material using flash program in the course of Inferential Statistics is very good and feasible to be used as learning media.